ROS-based Integration of Smart Space and a Mobile Robot as the Internet of Robotic Things - Uchechukwu, David; Siddique, Arslan; Maksatbek, Aizhan; Afanasyev, Ilya (IEEE, 2019)
The Internet of Robotic Things is a concept that is rapidly gaining traction in the robotics industry. As the field of robotics advances, one of the obstacles to its widespread adoption remains the high cost of purchasing and maintaining robot. Although the gap is continuously closing, robots these days cannot make decisions with the efficiency that humans can. People are spatially aware, and we can perceive and understand changes in the environment that robots are not capable of. This paper attempts to propose how a smart space can be implemented to increase the spatial awareness of a robot by providing more data to make better informed decisions. We focus on using the Robot Operating System (ROS) as a framework to integrate Smart Space and a mobile robot to expand the robots sensory information and make collision avoidance decisions.
Keywords: Computer Science